The effect of polymer/plasticiser ratio in film forming solutions on the properties of chitosan films - Fundo, Joana F. (2015)
In this work physical-chemical properties of chitosan/ glycerol film forming solutions (FFS) and the resulting films were analysed. Solutions were prepared using different concentrations of plasticising agent (glycerol) and chitosan. Films were produced by solvent casting and equilibrated in a controlled atmosphere. FFS water activity and rheological behaviour were determined. Films water content, solubility, water vapour and oxygen permeabilities, thickness, and mechanical and thermal properties were determined. Fourier transform infrared (FTIR) spectroscopy was also used to study the chitosan/glycerol interactions. Results demonstrate that FFS chitosan concentration influenced solutions consistency coefficient and this was related with differences in films water retention and structure. Plasticiser addition led to an increase in films moisture content, solubility and water vapour permeability, water affinity and structural changes. Films thermo-mechanical properties are significantly affected by both chitosan and glycerol addition. FTIR experiments confirm these results. This work highlights the importance of glycerol and water plasticisation in films properties.